Scrub Typhus Induced Thrombotic Thrombocytopenia: A Rare Case Report - Maharshi Patel; Sourya Acharya; Samarth Shukla; Shubham Nimkar; Sunil Kumar (Journal of Clinical and Diagnostic Research)
Scrub typhus is a zoonotic disease caused by Orientia tsutsugamushi. The bacterial infection is spread via Trombiculidae mites. A 50-year-old male patient was admitted with a complaint of fever, cough, breathlessness, and irrelevant talk for five days. The patient was chronic alcoholic and hypertensive for one year. After investigation patient was positive for scrub typhus. The patient had hepatitis, renal failure, thrombocytopenia, and right lower lobe pneumonia. The cause of thrombocytopenia in scrub typhus individuals could be the development of Thrombotic Thrombocytopenic Purpura (TTP), Disseminated Intravascular Coagulation (DIC), and thrombotic microangiopathy. In scrub typhus patients, TTP and Multiple Organ Dysfunction Syndrome (MODS) can be avoided with early diagnosis and effective treatment. Further research is warranted in such conditions to understand the molecular mechanism as well as to prevent mortality.